The level of commitment among intermediaries to SMEs : case study of SMEs at Tuaran, Sabah / Dk Fadiziahwati Pg. Othman - Pg. Othman, Dk Fadiziahwati (2013)
Small and Medium enterprise (SMEs) is one industry to growth up in activity development. The government and others agencies have been support the SMEs development activity to growth up in the market. There are three types development in growing industry which is the manufacture, services and agriculture industry. The purpose of the study was to examine the level of commitment among intermediaries to SMEs of small enterprise particularly in local products in the market. The study undertook a cross sectional survey design with a population of 138 respondents. Selfadministered questionnaires were used to collect responses. Measurements of the relationships of the study are information sharing, resources sharing and risk sharing was done and subjected to rigorous data processing and analysis using the relevant statistical computer software packages. Findings indicated that there were both positive and negative significant relationships between information sharing, resources sharing and risk sharing. Results from regression analysis showed three variables are information sharing, resource sharing and risk sharing were significant predictors of the relationship. The study recommends therefore, that since the model could only explain 42.7% in variance of the relationship in the level of commitment among intermediaries to SMEs of small enterprise at Tuaran, To study the role of intermediaries in information sharing , resources sharing and risk sharing are longitudinal study is more appropriated.